Karakteristik penderita neglected fractures yang dirawat di RSUP H. Adam Malik Medan periode Januari 2009-Desember 2010 - Onarisa Ayu (Fakultas Kedokteran USU, 2014)
Introduction : With the development of science and technology, the mobility in Indonesian are also higher and resulting in increased of motor vehicle accident so can increases the risk of of bone fractures. Mostly indonesian society still believe in the handling of fractures by bone setter, thus increasing the incidence of neglected fractures, which is often found in Haji Adam Malik General Hospital. This research purposes to know the characteristics and prevalence of neglected fractures in Haji Adam Malik General Hospital in January 2009 - December 2010.Methods : This is a retrospective descriptive study, in which data is extracted from the medical records of patients with neglected fractures were treated in Haji Adam Malik General Hospital in 2009-2010. Data are presented by frequency distribution tables and charts, and analysis in the analysis of meaning.Results : Neglected fractures patients were treated in the Haji Adam Malik General Hospital in 2009-2010 is more common in men (72.73%) and in the productive age (92.73%), with a low education level (37.73%) and previously have received treatment by bone setter (89.09%). The cause of the occurrence of fractures was traffic accident (98.18%), with the most location of fractures is femur (52.73%).Conclusion : The characteristics of patients neglected fractures in Haji Adam Malik General Hospital are common in men, with productive age, low education level, and has been handled by bone setter before came to Haji Adam Malik General Hospital. The most common cause of fracture due to traffic accidents and the most common location of fracture is femur. Key word : neglected fractures; cause of neglected fracture; neglected fracture in RSUP.H.Adam Malik